Sociodemographic characteristics of women in a public hospital in Campinas who underwent legal abortion due to sexual violence: cross-sectional study - Mutta, Danielle dos Santos; Yela, Daniela Angerame (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Sexual violence is increasingly frequent worldwide. The aim here was to evaluate the sociodemographic and psychological characteristics of women who requested legal abortion, at a public healthcare service, after suffering sexual violence. DESIGN AND SETTING: Retrospective descriptive study on 131 women who underwent legal abortion at the University of Campinas between 1994 and 2014, consequent to sexual violence. METHODS: The sociodemographic and psychological characteristics of women who were victims of sexual violence were evaluated from their medical records. The tests used to evaluate possible associations were the chi-square and/or Fisher’s exact test. RESULTS: The women’s mean age was 23 ± 9.2 years; 77.9% were white and 71.8% were single; 32.8% were students and 58.6% had employment outside of their homes. The majority reported that they did not know the aggressor (62.3%), but among the adolescents, 58% of the aggressors were known. The majority asked for abortion up to the 12th weeks of gestation (63.4%). Only 2.3% presented curettage complications. The psychological situation most frequently encountered was determined, in 34.4% of the cases before the abortion; and good in 32.8% after the abortion. CONCLUSIONS: There was greater occurrence of sexual violence among students and women who worked outside. Among the students, most of these were adolescents and had no previous sexual life. The teenagers were raped by a known aggressor.